Abdominal Wall Reconstruction: An Integrated Approach - Boukovalas, Stefanos; Sisk, Geoffrey; Selber, Jesse C. (Seminars in Plastic Surgery, 2018)
Abdominal wall reconstruction has undergone substantial evolution over the last few decades. The optimal method of repair should be tailored to each patient's unique condition; however, a general approach that integrates four major factors can be applied as a conceptual framework to most clinical scenarios. Major factors to be considered include selection of mesh material, mesh inset position and technique, selective component separation, and management of soft tissue. These topics are inextricably intertwined in the sense that each can have specific implications, and in some cases, a determinative impact on the other decisions. When the relationship among these four factors is appreciated and applied to patient management, the reconstructive surgeon can achieve consistent outcomes that reflect skill, experience, and understanding.
Keywords: abdominal wall reconstruction; ventral hernia repair; biologic mesh; synthetic mesh; component separation